The Role of Witness and Victim Protection Institutions in Fulfilling the Restitution Rights of Children Victims of Sexual Violence Crimes - Susandhi Sukatma; Tofik Yanuar Chandra; Amran Suadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The presence of the Witness and Victim Protection Agency as an institution that overcomes protection for Witnesses and Victims, at least provides fresh air for residents, especially children who face victims of intimate violence. It is intended as an effort to vent rights and provide encouragement to share comfort with witnesses and or victims that must be carried out by the LPSK or other institutions in accordance with the determination of this law. Looking at the meaning of the contribution of witnesses and or victims in making clear the issue of crimes to the importance of providing protection to witnesses and victims. There are also objectives that have been achieved in this preparation, namely to recognize and analyze the restitution rights of children victims of intimate violence crimes in crime law in Indonesia and to recognize and analyze the contribution of witness and victim protection institutions that act like state institutions that have the right to vent the restitution rights of children victims of intimate violence crimes in Indonesia. The research procedures used are normative juridical, with the approach of legislation, abstracts, problems, analysis of legal material used is qualitative. The results of the research prove that the basis for submitting restitution to children’s victims of intimate violence crimes has been regulated in Law No. 35 of 2014 concerning Child Protection and regulations regarding the method of applying retitution have also been regulated in Ruling Regulation No. 43 of 2017. This regulation on restitution was made to make it easier for the victim's child to plead for loss to the perpetrator of the crime of intimate violence. The method of applying restitution for victims of intimate violence crimes can be tried simultaneously by means of crimes, especially since it can be initiated from an early investigation submitted through the Witness and Victim Protection Agency (LPSK).